Systems of particles with interaction and the cluster formation in condensed matter - Krasnoholovets, V.; Lev, B. (Condensed Matter Physics, 2003)
We investigate the behaviour of a system of particles with the different character
of interaction. The approach makes it possible to describe systems
of interacting particles by statistical methods taking into account a spatial
nonhomogeneous distribution of particles, i.e. cluster formation. For these
clusters are evaluated: their size, the number of particles in a cluster, and
the temperature of phase transition to the cluster state. Three systems are
under consideration: electrons on the liquid helium surface, particles interacting
by the shielding Coulomb potential, which are found under the effect
of an elastic field (e.g. nucleons in a nucleus), and gravitating masses with
the Hubble expansion. Досліджено поведінку системи частинок з різними типами взаємодії. Пропонований підхід дозволяє описати системи взаємодіючих частинок статистичними методами, беручи до уваги просторову неоднорідність розподілу частинок, тобто, формування кластерів. Для кластерів оцінено: їхній розмір, число частинок в кластері і температуру фазового переходу до стану кластера. Розглянуто три системи: електрони на поверхні рідкого гелію; частинки, що перебувають в пружньому полі і додатково взаємодіють за допомогою екранованого кулонівського потенціалу (наприклад, нуклони в ядрі); частинки з гравітаційним потенціалом при наявності Хаблівського розширення.